Irreversible Lung Transformation Resulting from Damage In COVID-19 — Discourses and Examples of CT Images - A. S. Vinokurov; A. L. Yudin (Архивъ внутренней медицины)
The problem of the formation of irreversible residual changes after suffering viral lung damage with COVID-19 (COronaVIrus Disease 2019) after two years of the pandemic remains important and discussed. This is due to a large number of patients who have had a coronavirus infection (including those with a large amount of lung damage) and a possible unfavorable prognosis with a decrease in the quality and life expectancy. Given the fact that antifibrotic therapy has recently been actively used for a number of interstitial lung diseases (with idiopathic pulmonary fibrosis and systemic diseases), the question of the possible use of these drugs in case of an unfavorable outcome of COVID-19 is being considered. However, it is still not known exactly how often fibrosis develops in the outcome of a new coronavirus infection, and groups of patients who may have a poor prognosis in the form of an outcome in fibrosis have not been clearly identified.The review considers the pathogenetic aspects of the possible development of irreversible changes in patients with COVID-19, predisposing factors, as well as diagnostic features with an emphasis on CT scan with the authors’ own observations.